Carbon Asset Development Process - World Bank (World Bank, Washington, DC, 2021)
The Paris Agreement provides a framework for all countries - both developed and developing - to voluntarily adopt individual targets, elaborated in their nationally determined contributions (NDCs). This effectively introduces commitments on the country in the sectors covered by their NDCs. Consequently, there is a need for countries to ensure that mitigation outcomes (MOs) and their international transfer are accompanied by robust accounting. Beyond international climate markets under Article 6, the International Civil Aviation Organization (ICAO) decided to establish a global market-based mechanism, in the form of the carbon offsetting and reduction scheme for international aviation (CORSIA), to help achieve ICAO’s global goal of carbon-neutral growth. This note seeks to identify processes for the generation and transfer of carbon assets in post-2020 international climate markets and to suggest standard terminology in the carbon asset development cycle across key independent standards. The note builds on existing practices among different independent standards to streamline and harmonize process flows and ensure that country governments have greater clarity on the process for engaging in climate markets. This note reflects inputs from the informal working group on carbon assets, pilot transactions under different initiatives, as well as knowledge produced in relevant platforms.